Quantitative Study of Startup Valuation and Strategy Post 2022 Winter - Fajrin Rasyid, Muhamad; Sumirat, Erman; Aswin Rahadi, Raden (Journal of World Science, 2023)
Introduction: In 2022, the market capitalization of some publicly traded technology companies is declining. This period is commonly referred to as "winter" because it is more challenging for startups to get funding from investors. The study seeks to understand the impact of winter 2022 on the valuation and strategy of privately funded startups, focusing on five variables: sector, funding stage, relative market position, profitability, and founder's contribution/strength. Method: Quantitative analysis relies on survey responses from 180 startup founders in Indonesia who specialize in six industries: retail/e-commerce, fintech, agriculture/fisheries, healthcare, logistics, and education. Path Analysis is then applied to the data to determine the relationships between variables. Result: This research shows that profitability and founders' contributions/strengths impact startup valuation. Furthermore, relative market position and profitability have an impact on startup strategy. Finally, a decrease in valuation multiples for startups affects their strategy. Conclusion: This research can guide startup founders as they grow their businesses, especially in relation to the five variables listed above. Future research may be conducted on other variables, sectors, countries, or similar topics later/period.